2008
DOI: 10.1002/itdj.20086
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in enterprise system implementation in emerging economies: Insights from an exploratory study in Poland

Abstract: This article examines the difficulties experienced by organizations in emerging economies during the process of enterprise systems (ES) implementation. Building on research conducted among a few dozen experts representing ES suppliers and dealing with numerous ES implementations in Poland, this exploratory study discusses the characteristics of ES projects in emerging economies. After the incorporation of the Polish adopters' perspective, the analysis relates its findings with the results of prior research con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Slovenia and Slovakia, where companies seem to suffer from less support from vendors and tailored industry solutions. This finding is of some concern as research reported that firms in transition economies seek to maximise returns from investments by relying on external best practices (here exemplified with industry focuses solutions) and experience a lack of ITrelated skills in their internal workforce (Indjikian & Siegel, 2005;Soja, 2008).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Slovenia and Slovakia, where companies seem to suffer from less support from vendors and tailored industry solutions. This finding is of some concern as research reported that firms in transition economies seek to maximise returns from investments by relying on external best practices (here exemplified with industry focuses solutions) and experience a lack of ITrelated skills in their internal workforce (Indjikian & Siegel, 2005;Soja, 2008).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This type of research was also completed by Soja [19] in Poland, Colmenares [20] in Venezuela, Wu and Wang [21] in Taiwan, He and Brown [22] in China and Kamhawi in Bahrain [23].…”
Section: Critical Success Factors In It Projectsmentioning
confidence: 99%
“…Ngai identifies and discusses critical success factors in IT projects completed both in developed and developing countries [28]. The specific character of crucial success factors in developed and developing countries is analyzed by many researchers, including Soja [19] in Poland, Colmenares [20] in Venezuela, Wu and Wang [29] in Taiwan, as well as He and Brown [22] in China.…”
Section: Critical Success Factors In It Projectsmentioning
confidence: 99%
“…HEIs are having the department with limited IT staff available for managing IT resources and helping the institute to automate the academic processes. Therefore it is required to assess the capabilities of the available IT people, their knowledge, Skill and education while measuring ERP success [72]. This study is among the first of its kind to attempt to combine the effects of selected IT-related assets and resources on ERP success in higher education environment.…”
Section: Top Management Supportmentioning
confidence: 99%